A4.2 Adipocytes Modulate T Cell Function through Release of Lipids. (25th February 2013) - Ioan-Facsinay, Andreea; Kwekkeboom, Joanneke C; Westhoff, Sanne; Giera, Martin; Rombouts, Yoann; Huizinga, Tom WJ; Deelder, André; Kloppenburg, Margreet; Toes, René EM
Abstract : Background and Objectives: Obesity is characterised by the presence of inflammation in adipose tissue. Accumulation of several immune cell-types, including CD4+ T cells, has been previously reported in the increasing adipose tissue. This accumulation is also paralleled by changes in cytokine profiles and phenotype of the infiltrating cells. One of the possible mechanisms involved in these changes is the modulation of T cell function by tissue-resident adipocytes. Therefore, we investigated whether adipocytes derived from various adipose tissues can modulate CD4+ T cell cytokine production and proliferation and studied the mechanisms involved in this process. Materials and Methods: CD4+ T cells were purified from peripheral blood mononuclear cells using magnetic beads coated with anti-human CD4. Plate-bound anti-CD3 and soluble anti-CD28 antibodies were used to activate T cells. Adipocytes were isolated from IFP of OA patients by collagenase digestion and were either cultured with purified CD4+ T cells or were cultured in vitro for 24 hours in DMEM/F12 medium supplemented with 0.5% bovine serum albumin to generate adipocyte-conditioned medium (ACM). Cytokine/adipokine production was measured by intracellular cytokine staining (ICS), ELISA or cytokine multiplex. Lipids were isolated using hapten and lipid profiling was performed by liquid chromatography combined with mass spectrometry. Results: CD4+ T cells produced increased levels of IFNγ when activated in the presence of adipocytes. This effect is mediated by soluble mediators, as shown in transwell and adipocyte-conditioned medium (ACM) transfer experiments. Additionally, ACM induced increased proliferation of CD4+ T cells upon activation. Furthermore, adipose tissue contained more IFNγ-producing CD4+ T cells than peripheral blood of the same individuals, in 3 out of 3 cases tested, which indicates a possible in vivo relevance of our results. To investigate the possible molecular mechanisms involved in this effect, we separated the protein and lipid fraction of ACM. Surprisingly, despite previous data indicating that several adipocyte-derived proteins can modulate T cell function, we have found that the increased proliferation of T cells is mainly due to the lipids isolated from ACM. Further separation of these lipids based on polarity revealed that the modulatory effect is mainly confined to fractions containing free fatty acids. All identified fatty acids were able to individually enhance T cell proliferation. Conclusions: These data indicate that adipocytes can modulate CD4+ T cell function through release of soluble mediators. Remarkably, within the soluble mediators identified, lipids and especially free fatty acids are the most prominent modulators of T cell proliferation.